1981
DOI: 10.1128/jb.148.2.480-486.1981
|View full text |Cite
|
Sign up to set email alerts
|

Sporulation in Bacillus subtilis is independent of membrane fatty acid composition

Abstract: Growth and sporulation of a Bacillus subtilis mutant deficient in branched fatty acid synthesis (gene symbol bfmB) were examined. The mutant, which produces an acyl-coenzyme A:acyl carrier protein transacylase with reduced affinity for branched fatty acid primers, could grow in media containing any one of a wide range of low-molecular-weight fatty acids having branched, cyclic, saturated, or unsaturated carbon chains. The fatty acid composition of cellular lipids depended on the compound used to support growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…These results show that the amount of anteiso-fatty acids can be increased by growing spores in the presence of L-isoleucine. Changes in spore fatty acid composition have also been reported for B. subtilis (32) and B. megaterium (12) when spores were grown on either ~-keto acid or amino acid precursors of fatty acids. In both cases, the investigators observed that the ability of vegetative cells to form spores was unaffected by the added fatty acid precursors.…”
Section: Fatty Acid Composition Of Vegetative Cells and Spores Grown mentioning
confidence: 61%
“…These results show that the amount of anteiso-fatty acids can be increased by growing spores in the presence of L-isoleucine. Changes in spore fatty acid composition have also been reported for B. subtilis (32) and B. megaterium (12) when spores were grown on either ~-keto acid or amino acid precursors of fatty acids. In both cases, the investigators observed that the ability of vegetative cells to form spores was unaffected by the added fatty acid precursors.…”
Section: Fatty Acid Composition Of Vegetative Cells and Spores Grown mentioning
confidence: 61%